COVID-19 prevention strategies and compliance among postnatal adolescent mothers with postnatal depression and generalised anxiety in rural Malawi: a cross-sectional study - Sharyn Burns; Linda Portsmouth; Chimwemwe Pindani Tembo (BMJ Open)
Objectives This study examines the relationship between adolescent mothers’ mental health problems (postnatal depression and generalised anxiety) and adherence to COVID-19 public health prevention strategies in rural Malawi. It is part of a larger previously published study investigating the impact of social and cultural factors on the mental health in adolescent mothers.Design A cross-sectional study was conducted from September 2021 to March 2022. The Edinburgh Postnatal Depression Scale (EPDS) and the Generalised Anxiety Disorder-7 (GAD-7) were used to identify the risk of postnatal depression (PND) and generalised anxiety disorder (GAD), respectively. Participants also responded to questions about their perception of COVID-19 and how they practiced the recommended COVID-19 prevention strategies.Setting The study was conducted at a rural hospital in Lilongwe, Malawi.Participants Adolescent postnatal mothers aged 19 years and below, with children aged less than 1 year, who understood the study and could consent.Results Adolescent mothers (n=395) completed the researcher-administered survey. The mean age was±17 (SD 1.157). Most participants had recently given birth to their first child (91%, n=358). Almost half (45%, n=113) of participants agreed with the COVID-19 prevention strategies recommended by the Malawian government. However, overall adherence to public health COVID-19 prevention strategies, including hand hygiene practices, was low among adolescent mothers. Participants with probable GAD and probable PND were more likely to practice COVID-19 prevention strategies than participants with low GAD-7 or EPDS scores, except for restrictions on religious gatherings.Conclusions Adolescent perception of the potential threats or risks of COVID-19 was low. However, adolescents with probable PND and probable GAD reported higher adherence to some COVID-19 prevention strategies than adolescents without PND and GAD. The findings support the need for policies that integrate mental health within the public health response due to the potential direct and indirect effects the pandemic might have on perinatal mothers’ mental health. Additionally, recommended pandemic responses should be appropriate and relevant to the social environment.